Síndrome hemofagocítico asociado a dengue grave en una institución pediátrica de Cali - Colombia - Monica Lizet Pérez-Sánchez (Asociación Colombiana de Infectología, 2023)
Objective: to characterize pediatric patients with hemophagocytic syndrome associated with severe dengue in a pediatric institution in Cali-Colombia. Material and method: Descriptive observational study type case series. Seven patients under 18 years of age with a diagnosis of severe dengue and associated hemophagocytic syndrome were included, hospitalized at the Fundación Clínica Infantil Club Noel from December 2019 to November 2020. Results: Seven of 136 patients with severe dengue who met the diagnostic criteria for hemophagocytic syndrome were included. The majority were men (n = 6/7), with an average age of 7,7 years. The clinical manifestations were fever (n = 7/7), abdominal pain (n = 7/7), rash (n = 7/7), constitutional symptoms (n = 7/7) and hepatomegaly (n = 7/7). The most frequently compromised system was the respiratory system (n = 7/7) followed by the hemodynamic (n = 6/7) with the require-ment of mechanical ventilation (n = 5/7) and inotropia (n = 6/7). Discussion: All patients manifested with hepatosplenomegaly, thrombocytopenia, hyperferritinemia and hypofibrinogenemia, less presence of hemophagocytic cells, greater appearance of anemia and greater requirement of mechanical ventilation and inotropy compared to other studies (1,2). Conclusion: Children with hemophagocytic syndrome secondary to severe dengue infection may present multiorgan dysfunction, observing greater respiratory, hematological and renal compromise. Early diagnosis and treatment can improve prognosis.